Biological activity of heterocyclic systems based on functionally substituted 1,3,4-thia(oxa)diazoles (a review) - M. I. Lelyukh (The State Expert Center of the Ministry of Health of Ukraine, 2019)
1,3,4-Thiadiazole and oxadiazole hetetocycles are well-known pharmacophore scaffolds, which possess wide possibility for chemical modification and identified diverse pharmacological potential. Such essential and many-sided activities let to consider the mentioned heterocycles as ones of the crucial for expression of pharmacological activity, which confirm their importance for medicinal chemistry. Moreover, 1,3,4-oxadiazole cycle is a bioisostere for carboxylic, amide and ester groups, which mostly contribute to enhancement the pharmacological activity by participating in hydrogen bonding interactions with different enzymes and receptors. The aim of the work was analysis of literature data about biological activity of non-condensed heterocyclic systems based on 1,3,4-thia(oxa)diazole rings as promising objects for modern bioorganic and medicinal chemistry. In this study are presented the analysis of actual literature data about pharmacological activity of heterocyclic systems based on 1,3,4-thiadiazole. It has been established that mentioned scaffolds were identified as the main structural component of biological agents with antimicrobial, anti-inflammatory, analgetic, antitumor antitubercular and antiviral activity. Moreover, the combination of 1,3,4-thiadiazole or 1,3,4-oxadiazole core with various heterocycles led to synergistic effect in many cases. Thus, mentioned scaffolds are important heterocyclic fragments that are considered as promising structural matrices for the construction of new drug-likes molecules. An analysis of the biological activity of 1,3,4-thia(oxa)diazole derivatives was carried out, which allowed to confirm their versatile pharmacological potential. Obtained data can be considered as background for further in-depth studies of chemical and pharmacological properties such heterocyclic systems with possible application in medicine.